2007
DOI: 10.1111/j.1751-553x.2007.00931.x
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines on the insertion and management of central venous access devices in adults

Abstract: Central venous access devices are used in many branched of medicine where venous access is required for either long-term or a short-term care. These guidelines review the types of access devices available and make a number of major recommendations. Their respective advantages and disadvantages in various clinical settings are outlined. Patient care prior to, and immediately following insertion is discussed in the context of possible complications and how these are best avoided. There is a section addressing lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
197
0
18

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 233 publications
(216 citation statements)
references
References 88 publications
1
197
0
18
Order By: Relevance
“…Surgical cut-down and direct cannulation of a superficial vein for long-term access in adult patients should be discouraged, as studies have shown that it appears to be less efficient and clearly associated with an increased risk of infection [14,15,59]. Patients undergoing repeated long-term venous access procedures have a much higher frequency of thrombosed veins at the puncture site.…”
Section: Integration In Clinical Practicementioning
confidence: 99%
“…Surgical cut-down and direct cannulation of a superficial vein for long-term access in adult patients should be discouraged, as studies have shown that it appears to be less efficient and clearly associated with an increased risk of infection [14,15,59]. Patients undergoing repeated long-term venous access procedures have a much higher frequency of thrombosed veins at the puncture site.…”
Section: Integration In Clinical Practicementioning
confidence: 99%
“…Insertion of a CVC still carries the risk of improper placement and mechanical complications [47]. For this reason, a chest X-ray is advisable to verify the position of the catheter tip and exclude the possibility of iatrogenic pneumothorax (PTX) [48].…”
Section: Diagnosing Complications Of Central Venous Catheterizationmentioning
confidence: 99%
“…However, its performance was less promising with catheters introduced through the left internal jugular or left subclavian vein [56]. The main advantage of these checking systems is that they reduce the need to reposition the catheter after the postinsertion chest X-ray, which is still the reference method for verifying the correct placement [47]. However, there are no well-defined landmarks visible on chest X-rays that allow one to identify with certainty the boundary between the SVC and the right atrium.…”
Section: Diagnosing Complications Of Central Venous Catheterizationmentioning
confidence: 99%
“…It is designed for continuous use in patients hospitalized for days or weeks 1 . CVC is mainly indicated for patients with difficult access to peripheral veins, delivery of intravenous chemotherapy, potentially sclerosing medications, and total parenteral nutrition, repeated administration of blood products or blood components, repeated collection of blood samples, and hemodynamic monitoring 2,3 .…”
Section: ■ Introductionmentioning
confidence: 99%